Do traders strategically time their pledges during real-world Walrasian auctions? - Eaves, James; Williams, Jeffrey; Power, Gabriel J. (Journal of Banking & Finance, 2016)
Experimental research suggests the Walrasian tâtonnement auction encourages traders to under-reveal preferences, even encouraging initial pledges contrary to true desires, because pledges are not binding. We analyze the timing and characteristics of individual pledges and trades during 9604 auctions for redbeans conducted by the Tokyo Grain Exchange. We find no evidence of contrarian pledging and little evidence of under-revelation – as many traders over-reveal as under-reveal. Most traders pledge seriously from the beginning. Despite the considerable heterogeneity in pledging behavior across individual traders, these differences appear to have no relationship with traders’ profits, nor do they appear to affect the achievement of equilibrium.